Implementing an evidence-based somatic acupressure intervention in breast cancer survivors with the symptom cluster of fatigue, sleep disturbance and depression: study protocol of a phase II randomised controlled trial - Wang, Tao; Tan, Jing-Yu (Benjamin); Liu, Xian-Liang; Zheng, Si-Lin; Zhao, Isabella; Eliseeva, Sabina; Polotan, Mary Janice; Cheng, Hui-Lin; Huang, Hou-Qiang (BMJ open, 2022)
IntroductionThe fatigue-sleep disturbance-depression (FSD) symptom cluster, as one of the most common symptom clusters in breast cancer (BC) survivors, can significantly decrease patients’ quality of life. Since the management of the FSD symptom cluster has been unsatisfactory with the use of pharmacological treatments alone, non-pharmacological approaches have, therefore, been recommended. Somatic acupressure (SA) is a promising approach given its potential benefits of cancer-related symptom alleviation and the convenience of self-practice. However, research evidence on using acupressure to manage the FSD symptom cluster has been limited. The proposed trial aims to examine the feasibility and preliminary effects of an evidence-based SA intervention for FSD symptom cluster management in BC survivors.Methods and analysisThis study will be a phase II randomised controlled trial with three study arms and 1:1:1 allocation. Fifty-one early-stage BC survivors who are experiencing the FSD symptom cluster will be randomly assigned to a true SA group, a sham SA group or a usual care group. All participants will receive an education booklet regarding FSD symptom cluster management advice as the usual care package. The participants in the true SA group will additionally receive a 7-week self-administered SA intervention. The participants in the sham SA group will additionally receive self-administered light acupressure at non-acupoints with the same frequency, session and duration as the true SA group. The primary outcomes will be feasibility outcomes related to subject recruitment and completion of study questionnaires and interventions. The secondary outcomes will be the effects of SA on fatigue, sleep disturbance, depression and quality of life. Descriptive statistics will be used to present all the outcomes. The secondary outcomes will be analysed using an intent-to-treat approach.Ethics and disseminationEthical approvals of this trial have been granted by the Human Research Ethics Committee at Charles Darwin University (H19017) and the Clinical Trial Ethics Committee at The Affiliated Hospital of Southwest Medical University (KY2019039). Findings from this trial will be published in peer-reviewed journals and presented at professional conferences.Trial registration numberThis trial was registered at ClinicalTrials.gov and the registration number is NCT04118140, with the stage at Recruiting.